A Path Analytic Model of Socio-Psychological Attributes on the Performance of College Students in Mathematics (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper used path analysis in determining the best causal model of the mathematics performance of the students.The participants of the study were non-math major college students of Bukidnon State University. The results revealed thatpaths of students’ engagement, self-efficacy, math anxiety, and math attitude to their mathematics performance are significant.Furthermore, all attributes have indirect path to the mathematics performance except for the students’ engagement. Based onthe results, students’ engagement, self-efficacy, and mathematics attitude have a positive effect on the students’ mathematicsperformance. However, mathematics anxiety can negatively affect the students’ performance in mathematics.